Validation of candidate gene-based EST-SSR markers for sugar yield in sugarcane - Divakar, S.; Jha, Ratnesh Kumar; Kamat, D. N.; Singh, Ashutosh (Frontiers in Plant Science, 2023)
Sugarcane (Saccharum spp.) is a widely cultivated crop that fulfils approximately 75 % of sucrose demand worldwide. Owing to its polyploidy and complex genetic nature, it is difficult to identify and map genes related to complex traits, such as sucrose content. However, association mapping is one of the alternatives for identifying genes or markers for marker-assisted selection. In the present study, EST-SSR primers were obtained from insilico studies. The functionality of each primer was tested using Blast2Go software, and 30 EST-SSR primers related to sugar content were selected. These markers were validated using association analysis. Total 70 F1 diverse genotypes for sugar content were phenotypes with two check lines. All parameters related to sugar content were recorded. The results showed significant variation between the genotypes for sugar yield traits such as Brix value, purity, and sucrose content, etc. Correlation studies revealed that the Brix%, sucrose content and sucrose recovery were significantly correlated. Association analysis was performed using Mixed Linear Model (MLM) to avoid false positive associations. Association analysis revealed that the SEM 407 marker was significantly associated with Brix% and sucrose content. SEM 407 primers are putatively related to diphosphate-fructose-6-phosphate 1- phosphotransferase which is associated with brix% and sucrose content. This functional marker can be used for marker-assisted selection for sugar yield traits in sugarcane that could accelerate the sugarcane breeding program.